Mathematical epidemiology of infections diseases model building ,analysis,and interpretation - Diekmann, O. (Wiley series in mathematical and computational biology, 2000)
Provides systematic coverage of the mathematical theory of modelling epidemics in populations, with a clear and coherent discussion of the issues, concepts and phenomena. Mathematical modelling of epidemics is a vast and important area of study and this book helps the reader to translate, model, analyse and interpret, with numerous applications, examples and exercises to aid understanding